2015
DOI: 10.1016/j.compfluid.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Direct numerical simulation of cylindrical particle-laden gravity currents

Abstract: numerical simulation of cylindrical particle-laden gravity currents. Computers and Fluids, Elsevier, 2015, 123, pp.23-31. <10.1016/j.compfluid.2015 b s t r a c tWe present results from direct numerical simulations (DNS) of cylindrical particle-laden gravity currents. We consider the case of a full depth release with monodisperse particles at a dilute concentration where particle-particle interactions may be neglected. The disperse phase is treated as a continuum and a twofluid formulation is adopted. We pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The present code has been utilized in the context of turbulent turbidity currents in a channel (e.g., Cantero et al, ) and density‐driven flows (e.g., Zgheib et al, , ). More recently the IBM in this code has been extensively tested and used in the context of flow over isolated particles and through a random array of spherical particles (e.g., Akiki, Jackson, et al, , ; Akiki, Moore, et al, ).…”
Section: Turbulent Flow Over a Wavy Bed: A Validation Casementioning
confidence: 99%
“…The present code has been utilized in the context of turbulent turbidity currents in a channel (e.g., Cantero et al, ) and density‐driven flows (e.g., Zgheib et al, , ). More recently the IBM in this code has been extensively tested and used in the context of flow over isolated particles and through a random array of spherical particles (e.g., Akiki, Jackson, et al, , ; Akiki, Moore, et al, ).…”
Section: Turbulent Flow Over a Wavy Bed: A Validation Casementioning
confidence: 99%
“…Das et al studied flow and heat transfer of randomly packed spherical particles in slender fixed bed with DNS method, and models of pressure drop and Nusselt for wall‐to‐bed heat transfer were proposed. Zgheib et al studied the cylindrical particle‐laden gravity currents using DNS method. The results showed that vortex structures have a strong influence on wall shear‐stress and deposition pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Circulating fluidized beds (CFD) involving cylindrical particles are often encountered in industrial processes such as direct combustion of biomass straws, molding and drying of cylindrical pills, and molding and machining of composite materials of short fibres. Orientation of cylindrical particles in these processes is of utmost importance as it directly determines the distribution of solids and hence the hydrodynamics of the gas–solid flow which in turn dictates the overall performance of the system. , However, a good understanding of the theory underlying the gas-cylindrical particle flow is largely lacking due to the complex geometry of cylindrical particles, in particular in the presence of turbulence.…”
Section: Introductionmentioning
confidence: 99%